Standards for Including Scientific Evidence in Restrictions on Freedom of Movement: The Case of EU Covid Certificates Scheme - Danaja Fabcic Povse; Paul Quinn; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
Compared to previous secondary legislation, Article 11 of the Digital Covid Certificates regulations was remarkably explicit in its requirement for Member States to consider scientific evidence when restricting free movement for the certificate holders. However, we argue in this Article that the regulations achieved a partial codification of the existent case law of the CJEU rather than imposing any additional requirements. Namely, the case law had already required Member States to rely on scientific evidence that reflects the international consensus, that is relevant and up to date, and that the evidence had to demonstrate by means of a risk assessment a real risk to the public health. We also discuss these findings in the light of the proportionality and precautionary principles and suggest that understanding the evolution of the EU legal order’s evidentiary requirements is useful in the light of the legislator’s claim of objective and rational policy-making procedures in public health and other crises.